The Concept of the People of the Book (Ahl Al-Kitab) in Islamic Religious Tradition - Sabjan, Muhammad Azizan; Mat Akhir, Noor Shakirah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2005)
The issue of the People of the Book has long been of central significance to Islam and later to the study of comparative religion. Many Muslim and European scholars have hence taken close heed of the People of the Book and their role as the holders of sacred books. The question of the People of the Book becomes more crucial when Muhammad 'Abd al-Karim al-Shahrastani (d.548/1153) develops another category identified as "Man Lahu Shubhat Kitab" (those who possess doubtful sacred scrolls) or "Ahl Shubhat Kitab" (the People of a Dubious Book), the term that may be considered similar to that of al-Shahrastani. However, the focus of the present study will be the problem of "Ahl al-Kitab" (the People of the Book) and their religions, i.e., Judaism and Christianity, as seen from the Qur'an and Islamic Religious Tradition. Before proceeding with the analytical study of the People of the Book, it is vital to turn first to the study of some misconceptions concerning the so-called three "Abrahamic" Faiths. In a strict sense, it is only together with a proper understanding of such misconceptions that one can easily understand the nature of the People of the Book in the Qur'an and Islamic Religious Tradition.